Developing Immersive Virtual Reality-Based Experiential Learning to Improve Communication and Problem-Solving Skills of Slow Learners in Inclusive Elementary Schools - Imada Cahyani Elvirawati; Reza Rachmadtullah; Cholifah Tur Rosidah (STAI Hubbulwathan Duri, 2026)
Slow learners in inclusive elementary schools often experience difficulties in communication and problem-solving, partly due to limited access to interactive and contextual learning media. This study aimed to develop and evaluate an Immersive Virtual Reality (IVR)-based experiential learning model to enhance these skills.The study employed a Design-Based Research approach comprising needs analysis, design, implementation, and reflection phases. Participants included accompanying teachers and slow learner students from several inclusive elementary schools in East Java. Data were collected through expert validation sheets, observations, interviews, questionnaires, and pre-test and post-test instruments. Quantitative data were analyzed using paired sample t-tests, while qualitative data supported the refinement of the intervention.Expert validation indicated high feasibility, with average scores ranging from 4.7 to 4.8 across all aspects, categorized as “very worthy,” including content suitability, visual design and interactivity, integration of experiential learning principles, usability, and appropriateness for slow learners. Effectiveness testing revealed significant improvements in students’ communication skills (mean scores increasing from 66.7 to 83.0) and problem-solving skills (from 69.4 to 87.7), with p = 0.000 0.05 for both variables.The findings demonstrate that IVR-based experiential learning is both feasible and effective in enhancing communication and problem-solving skills among slow learners. By offering immersive, interactive, and meaningful learning experiences, this approach supports skill development in inclusive settings and highlights the potential of technology-enhanced pedagogy for diverse learners.